Military Networks at the Extremes of Empire: The Che of Chile and the Puebloans of the United States. - Sauer, Jacob J. (Ethnohistory, 2020)
At the northern and southern ends of the Spanish "Empire," two cultures of similar sociopolitical complexity violently removed Spanish invaders from their ancestral territory. The Che of southern Chile militarily engaged the Spanish in the mid-sixteenth century and eventually forced the Spanish to abandon their colonization attempts. The Puebloans of the southwestern United States also forced the Spanish to flee from Puebloan territory in 1680, but by 1696, Puebloan territories returned to Spanish hegemony. This article compares some of the reasons why the Che maintained independence for more than 350 years while Puebloan independence lasted 16, examining the military power networks of the Che and Puebloans and the timing of resistance to Spanish incursion. These comparisons highlight some of the diverse reactions of foreign groups and how connections between peoples affect how individuals and communities react to outside influences.